2017
DOI: 10.1186/s12888-016-1175-0
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic group CBT vs. standard group CBT for depression, social anxiety disorder and agoraphobia/panic disorder: Study protocol for a pragmatic, multicenter non-inferiority randomized controlled trial

Abstract: BackgroundTransdiagnostic Cognitive Behavior Therapy (TCBT) manuals delivered in individual format have been reported to be just as effective as traditional diagnosis specific CBT manuals. We have translated and modified the “The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders” (UP-CBT) for group delivery in Mental Health Service (MHS), and shown effects comparable to traditional CBT in a naturalistic study. As the use of one manual instead of several diagnosis-specific manuals could simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…The aim of the present research is to replicate and extend previous findings from Spitzer and colleagues, while also comprehensively presenting our concerns regarding the measure. A critical reexamination and discussion of the RFQ-8 appears to be of particular importance given that researchers are increasingly adopting the measure for primary investigations of the mentalizing construct (e.g., Agostini et al, 2019;Badoud et al, 2018;Berthelot et al, 2019;Brugnera et al, 2020;Carlone & Milan, 2020;Cosenza et al, 2019;de Meulemeester et al, 2017de Meulemeester et al, , 2018Euler et al, 2019;Gambin et al, 2020;Huang et al, 2020;Li et al, 2020;Macfie et al, 2020;Morosan et al, 2019Morosan et al, , 2020Perroud et al, 2017;Sacchetti et al, 2019;Salaminios et al, 2020;Scandurra et al, 2020) or as an outcome measure for evaluating psychotherapy effectiveness (e.g., Arnfred et al, 2017;Derks et al, 2019).…”
mentioning
confidence: 99%
“…The aim of the present research is to replicate and extend previous findings from Spitzer and colleagues, while also comprehensively presenting our concerns regarding the measure. A critical reexamination and discussion of the RFQ-8 appears to be of particular importance given that researchers are increasingly adopting the measure for primary investigations of the mentalizing construct (e.g., Agostini et al, 2019;Badoud et al, 2018;Berthelot et al, 2019;Brugnera et al, 2020;Carlone & Milan, 2020;Cosenza et al, 2019;de Meulemeester et al, 2017de Meulemeester et al, , 2018Euler et al, 2019;Gambin et al, 2020;Huang et al, 2020;Li et al, 2020;Macfie et al, 2020;Morosan et al, 2019Morosan et al, , 2020Perroud et al, 2017;Sacchetti et al, 2019;Salaminios et al, 2020;Scandurra et al, 2020) or as an outcome measure for evaluating psychotherapy effectiveness (e.g., Arnfred et al, 2017;Derks et al, 2019).…”
mentioning
confidence: 99%
“…Data from a recently finalized multicentre, randomized controlled trial [21] investigating the relative efficacy of group diagnosis-specific versus transdiagnostic cognitive-behavioral therapy for anxiety disorders or depression support the meta-analytic findings on social phobia. In this trial, 291 patients with anxiety disorders or depression received standardized treatment programs in three Danish mental health services, and the results suggested that only half of the patients no longer met diagnostic criteria for their principal diagnosis by the end of treatment [22].…”
Section: Background Introduction and Rationalementioning
confidence: 73%
“…The current study aimed to explore the role of group cohesion in patients’ experiences of group CBT for anxiety and depression in an MHS context. Furthermore, the study set out to compare data from 12 patients who had participated in mixed-diagnoses, transdiagnostic CBT groups with the data from 11 patients who had participated in diagnosis-specific group CBT for MDD, social anxiety disorder or panic disorder/agoraphobia [ 26 ]. When discussing the results in the following sections, we define group cohesion as a feeling of belonging to the group and being mutually supported and supportive of the group.…”
Section: Discussionmentioning
confidence: 99%